El arte nuevo de hacer... Kabuki: Las teorías lopescas sobre el teatro y sus paralelismos en el Kabuki nipón - Cid Lucas, Fernando (2012)
This paper examines the main proposals in El arte nuevo de hacer comedias en este tiempo (1609), written by Félix Lope de Vega y Carpio (1562-1635), and the coincidences of these with the inner manner in Kabuki, with which it shares interesting resemblances.